Hubungan Sosial Ekonomi dan Pola Makan dengan Kejadian Kekurangan Energi Kronis (KEK) pada Ibu Hamil di Wilayah Kerja Puskesmas Nambo Kota Kendari - Musaddik, Musaddik; Rizka Putri, Linda Ayu; Muhim, Habib Ihsan (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2022)
Chronic Energy Deficiency (CED) is a nutritional problem and a sample of 35 people was obtained with a saturated sample. Data were analyzed using Chi-Square test. The results showed that of the 22 pregnant women with low socioeconomic status, some tended to be pregnant and experienced an increase. The prevalence of CED at the Nambo Health Center in 2019 was 45.1% and in 2020 it was 49.7%. The purpose of this study was to determine the relationship between family socioeconomic and dietary patterns with the incidence of CED in pregnant women. Analytical survey research design, cross sectional study approach. The population was all pregnant women who were at the Nambo Health Center as many as 35 people, 59.1% experienced CED. Furthermore, of the 15 pregnant women whose diet is adequate, most 80.0% do not have CED. The results of the Chi-Square test obtained a p value of 0.012 for socioeconomic and 0.018 for a diet with Chronic Energy Deficiency (CED) in Pregnant Women. The conclusion of the study is that there is a relationship between family socioeconomic status and diet with the incidence of chronic energy deficiency (CED) in pregnant women. Suggestions for the Nambo Health Center, to provide education about CED to pregnant women so that they can regulate their diet and for further researchers, to provide assistance to pregnant women with CED to control nutritional intake during pregnancy.